2021
DOI: 10.3390/jcm10194528
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Surface Texture Analysis of Fluoride’s Effect on Enamel Erosion

Abstract: Enamel erosion has become a common clinical finding that often impairs dental esthetics and function. In the current study, we aimed to implement the three-dimensional surface texture analysis (3DST) method to explore the protective effect of fluoride on surface texture prior to erosive conditions. For each of the 50 teeth used in this study, the polished buccal enamel surface was divided into three separate areas: the first area was untouched polished enamel, the two other surfaces were immersed in 0.3% citri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Erosive tooth wear was analysed by widefield confocal microscopy. Confocal scanning microscopy is increasingly used in the last decade to analyse surface texture parameters and quantify surface loss with a high sensitivity 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Erosive tooth wear was analysed by widefield confocal microscopy. Confocal scanning microscopy is increasingly used in the last decade to analyse surface texture parameters and quantify surface loss with a high sensitivity 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This experimental approach was not possible in this study, as we aimed to study the natural fluorotic surfaces, which did not allow for any processing of the enamel surfaces. [23][24][25] It is possible that different results could have been found if fluorosis severity levels higher than those studied (TF > 4) were to be considered. This was not done in this study, as our main focus was on non-cavitated enamel surfaces.…”
Section: Discussionmentioning
confidence: 96%
“…Citric acid was chosen as it is commonly found in fruit juice drinks and most carbonated beverages and is generally accepted as the standard acid in several models for the simulation of dental erosion. 18,23,24 While caries lesion formation involves a slow diffusion of dissolved minerals that combine with a liquid phase partially saturated with regard to tooth mineral, frequently creating conditions for remineralization in response to demineralization events, 25 the transport of ions dissolved by demineralization is much faster in dental erosion, 26 so that mineral loss involves more intensively the enamel subsurface in caries and is more concentrated at the enamel surface in erosion. It has been shown that the higher contrast in fluoride content between normal and fluorotic enamel is found at the enamel subsurface, 3 which would favor a higher impact of fluorosis on caries (subsurface phenomenon) than in dental erosion (surface phenomenon).…”
Section: Discussionmentioning
confidence: 99%
“…The cavity volume and diameter are not taken into account in this measurement because it only takes the height parameters into account. Consequently, it can be claimed that the texture of the surface cannot be properly described by using only one value to explore the surface topography [24]. In our study, Rz was also measured to evaluate deep scratches along with Sa and Ra.…”
Section: Discussionmentioning
confidence: 98%